(RE) utilization of scrap metal-mechanical branch in front of environmental sustainability - Santos, Lucas Almeida dos; Marzall, Luciana Fighera; Godoy, Leoni Pentiado (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In today’s world the theme of sustainability becomes increasingly important for the operation of companies. Thus, Brazilian enterprises are seeking to adapt to this new market reality, seeing improvements in their processes which reflect on great production performance and minimizing the percentage of waste. In light of these indices, there was an action research in an industry metallurgical industry midsize central region of Rio Grande do Sul, specializing in the manufacture of laser cut parts, serving the market at a national level. Thus, it was necessary to use historical data of the organization related to the consumption of raw material, steel, plus an understanding of how productivity management in the organization occurs. As a result it was possible to verify that the waste material is around 31%. Through this result, we generated actions to seize the flaps resulting from the production process, in search of higher yield of raw material used. Moreover, we have that, the decrease of waste material used by the company, makes it more competitive with respect to the laser cutting market in addition to adjusting the trend of the world market, as environmental sustainability.